GALUR-GALUR MUTAN PADI PADA KONDISI SAWAH TADAH HUJAN - Ali Imamuddin; Untung Susanto; M. Yamin Samaullah (Agroswagati Jurnal Agronomi, 2019)
Evaluation some mutant rice lines on rainfed area. Some mutant rice lines are expected to have good adaptability in the rainfed areas. Evaluation of drought tolerant rice lines in the rainfed land has been conducted in District Jakenan, Pati, Central Java in DS 2014. The Study used a randomized experimental design with 2 replications treatment 38 drought tolerant mutant rice lines and four varieties for the check. Mutant lines were evaluated coming from Co60 gamma-rays against Inpari 13. Varieties for check used is Inpari 13, Inpari 10, Inpari 23, and Situ Bagendit. Seedling age 20 days after sowing of each line and varieties grown as much as 1-3 seeds per hole on a plot measuring 2 m x 5 m with a spacing of 20 cm x 20 cm. Watering depends on rain and pump water from rainwater reservoir. The results showed that the lines tested had noticeable difference to the five agronomic characters were observed, but no real character number of productive tillers. A total of 13 genotypes showed higher yields than all varieties. Two genotypes showed a different result was significantly higher than Inpari 13 are BP17280M-26D-1-SKI-1-IND-1 (3.89 t / ha) and BP17280M-24C-2-1-SKI-1-IND- 1 (3.54 t / ha). While the best varieties Inpari 13 and Situ Bagendit achieve respectively 2.88 t / ha and 3.04 t / ha. The average best genotypes age at 50% flowering is 68-70 DAS and harvest age is HSS 98-104. With this result is expected to give a great chance on the tests subsequent to the development of new varieties of rainfed rice.